A Historical Study of Prosperity Gospel Preaching in Nigeria, 1970-2014 - Kitause, R. Habila (University of Nigeria, 2017)
Prosperity gospel preaching is a double-barrelled socio-religious phenomenon which is fast becoming one of the most significant expressions of Christianity and is remarkably wielding a pervasive influence within the Nigerian religious space. As a dominant strain of popular spirituality, prosperity gospel has remained a major socio-cultural force in Nigeria. The study generally attempts a comprehensive study of prosperity gospel in Nigeria and specifically, it examines the impacts and conflicting views on the reasons for the shift in emphasis of prosperity preachers from asceticism to materialism. The study is crafted using phenomenological approach for its richness and objectivity. The results show that prosperity preaching is currently the major preoccupation of the Pentecostals and has challenged endemic poverty in Nigeria through its emphasis on spiritual and economic empowerment programmes of the prosperity purveyors which is engendering remarkable social, economic and spiritual transformation in the Nigerian society. But the Pentecostals’ undue emphasis on giving as an investment for future prosperity occasioned by wrong interpretation of Scriptures by prosperity preachers resulting to misinformation and misapprehension of people about prosperity has negatively impacted on a broad spectrum of the Nigerian Christians and churches financially, socially and spiritually. At the moment, there seems to be a gradual paradigm shift in the orientation of people from hard labour to idleness and from holiness to worldliness in Nigeria. In view of the foregoing, the work, in recognition of some positivism of prosperity gospel draws its conclusion that the impacts of prosperity gospel are more damaging than beneficial in Nigeria.
free